Formulation and Characterization of Imatinib Mesylate Liposomes in Gel for Intraarticular administration (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Intra-articular administration of drug loaded in liposomal gel directly in joints provides spatial and prolonged local action by minimizing drug particle clearance from the synovial cavity. The objective of the present study was to prepare imatinib mesylate (IMT) containing liposomes, which were further loaded in xanthan gum gel for intraarticular administration to increase the duration of drug release. Liposomes were prepared by using different ratios of 1,2-Dierucoyl-sn-glycero-3-phosphatidylcholine, 1,2-Dipalmitoyl-sn-glycero-3-phospho-rac-glycerol and cholesterol using thin film hydration method. The liposomes were evaluated for entrapment efficiency, surface charge potential and size distribution to establish formulation composition and process parameters. Light microscopy and scanning electron micrographs of the liposomes showed the spherical topography of the prepared liposomes. Viscosity and gel strength of the gel loaded with IMT containing liposomes was evaluated. In-vitro release study showed that liposome gel formulations could significantly extend the drug release compared with conventional gel and liposome formulations. The formulation was studied for stability over a period of 6 months for pH, viscosity, drug release up to 7 days at two different conditions i.e. 2 to 8°C and 25 ± 2°C and 60% RH ± 5% RH. Analytical results are more promising and no significant difference was observed in these parameters when the formulation was stored at 2 to 8℃. In summary, liposome gel is expected to be an efficient cargo for intra-articular drug delivery of Imatinib mesylate.